An Electronic Checklist Improves Transfer and Retention of Critical Information at Intraoperative Handoff of Care. (January 2015) - Agarwala, Aalok V.; Firth, Paul G.; Albrecht, Meredith A.; Warren, Lisa; Musch, Guido
<x xml:space="preserve">Abstract</x> BACKGROUND: Communication failures are a significant cause of preventable medical errors, and poor-quality handoffs are associated with adverse events. We developed and implemented a simple checklist to improve communication during intraoperative transfer of patient care. METHODS: A prospective observational assessment was performed to compare relay and retention of critical patient information between the outgoing and incoming anesthesiologist before and after introduction of an electronic handoff checklist. Secondary measurements included checklist usage and clinician satisfaction. RESULTS: Sixty-nine handoffs were observed (39 with and 30 without the checklist). Significant improvements in the frequency of information relay occurred with checklist use, most notably related to administration of vasopressors and antiemetics (85% vs 44%, P = 0.008; 46% vs 15%, P = 0.015, respectively); estimated blood loss and urine output (85% vs 57%, P = 0.014; 85% vs 52%, P = 0.006, respectively); communication about potential areas of concern (92% vs 57%, P = 0.001), postoperative planning (92% vs 43%, P < 0.001), and introduction of the relieving anesthesiologist to the operating team (51% vs 3%, P < 0.001). When queried after the handoff, relieving anesthesiologists more frequently knew the antibiotic (97% vs 75%, P = 0.020), muscle relaxant (97% vs 63%, P = 0.003), and amount of fluid administered (97% vs 72%, P = 0.008) when the checklist was used. Voluntary use of the checklist occurred in 60% of the handoffs by the end of the observation period (99% control limits: 58%–75%.). Clinicians who reported using the checklist in at least two-thirds of their handoffs reported higher satisfaction with quality of communication at handoff (P = 0.003). CONCLUSIONS: An electronic checklist improved relay and retention of critical patient information and clinician communication at intraoperative handoff of care.